Subepithelial Connective Tissue Grafting Around Dental Implants: From Established Soft-Tissue Benefits to Uncertain Marginal Bone Effects - Oskar Pieniak; Bartłomiej Górski (Journal of Clinical Medicine, 2026)
Subepithelial connective tissue grafting (SCTG) is widely used to increase peri-implant mucosal thickness and buccal soft-tissue volume, but its relevance to marginal bone stability remains uncertain. This narrative review examines whether SCTG provides clinically meaningful effects beyond soft-tissue phenotype modification, with particular emphasis on marginal bone level (MBL). Evidence was synthesized by separating direct intervention studies of SCTG or peri-implant soft-tissue augmentation from indirect studies relating baseline phenotype dimensions to subsequent tissue behavior. Randomized and comparative studies consistently show increases in mucosal thickness and soft-tissue volume and, in selected indications, improved contour and mucosal-margin stability. By contrast, MBL findings are heterogeneous. Greater mucosal thickness or supracrestal tissue height has been associated with less crestal remodeling, particularly during early healing; however, these prognostic associations do not establish that surgical thickening with SCTG reproduces a bone-preserving effect. Long-term trials further show that improved mucosal-margin stability can coexist with little or no clear between-group difference in MBL. Current evidence therefore supports SCTG primarily as a phenotype-modification and reconstructive procedure. A direct, independent, durable SCTG-mediated effect on marginal bone preservation remains biologically plausible but unproven; the evidence identified in this review does not support routine SCTG solely as prophylaxis for MBL preservation.